Об эндемике черноморского бассейна — Eucyclops persistens sp. n. (Crustacea, Copepoda) - Монченко, В.И. (Вестник зоологии, 1978)
A new species E. persistens sp. n. from oligohaline estuarian interstitial of the two Caucasus rivers is described and its drawings are given. It appears to be most closely related to E. orthostylis (the Caspian Sea), but differs from the latter and other species in many characters: some shortened parts — furcal rami (middle indices 4.5) without outer serra, antennulae, bristle on the first exopod joint of P₄ and lateral spines on distal joint of endopod P₄, very elongated innermost apical furcal seta which is almost equal to furcal rami and twice as long as outermost spinelike appendage. The key for 7 species of Eucyclops from the Soviet Union fauna is given.